The therapeutic effect of glucocorticoids on type II respiratory failure, heart failure, and massive pericardial effusion caused by hypothyroidism: A case report - Wang, Jingyue; Li, Xiangjun; Shen, Botao; Wang, Shipeng; He, Jiahuan; Wang, Yushi (Frontiers in Pharmacology, 2022)
Background: Hypothyroidism is a disease commonly observed in outpatient clinics but can occasionally cause severe cardiovascular and respiratory diseases requiring hospitalization. Case report: The patient reported herein suffered from heart failure, massive pericardial effusion, type II respiratory failure, and hypothyroidism. There was no related basic diseases of respiratory and cardiovascular system in the past. She failed to be weaned from invasive ventilation multiple times after routine treatment and was finally successfully weaned on day five of receiving the combination therapy of a high-dose methylprednisolone intravenous drip and levothyroxine oral administration. Conclusion: This case report indicates that hypothyroidism may be a cause of type II respiratory failure, heart failure, and massive pericardial effusion without cardiac tamponade and that a combination of levothyroxine and corticosteroids could effectively treat the disease. Clinical workers should consider the role of thyroid function in diagnosis, and the admission team should include this aspect in the monitoring scope. Moreover, the role of hormones in the treatment of patients with severe hypothyroidism should not be ignored, and timely treatment should be provided.